Copper-catalyzed olefinic trifluoromethylation of enamides at room temperature - Feng, Chao (2013)
Copper-catalyzed olefinic trifluoromethylation and oxytrifluoromethylation of enamides is reported. The direct olefinic C–H trifluoromethylation constitutes an efficient method for the stereoselective synthesis of β-trifluoromethyl substituted enamides.